Integration of Tarekat teachings in the Islamic education curriculum: a case study at the Miftahul Huda Gading Islamic Boarding School in Malang - Amboro, Kamas Wahyu (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
Islamic education in Indonesia is closely related to pesantren. Islamic boarding schools in Indonesia have varied styles. almost all pesantren have tasawuf values but not all pesantren teach tarekat. Even though the tarekat is something that becomes the teachings of Sufism. So that research on the integration of tarekat in the education curriculum is very important to study to find out how the integration of tasawuf is in the Islamic education curriculum. The approach used in this study is a qualitative approach. The data collection technique in this study was carried out with documentation and the data analysis technique used in this research was the Miles and Huberman model. The results of this study are that the tarekat taught in this pesantren is the qodiriyah wa Naqsabandiyah tarekat, there is formal and non-formal education, and there is integration of the tarekat's teachings into the Islamic education curriculum. Teaching tarekat is carried out outside of formal learning such as sunnah recitation, dhikr 165 times after obligatory prayers, khususiyah and manaqiban.Â Pendidikan islam di Indonesia sangat erat kaitannya dengan pesantren. Pesantren di Indonesia memiliki corak yang variatif. hampir semua pesantren memiliki nilai-nilai tasawuf tetapi tidak semua pesantren mengajarkan tarekat. Padahal tarekat merupakan sesuatu hal yang menjadi ajaran tasawuf. Sehingga penelitian tentang Integrasi tarekat dalam kurikulum Pendidikan menjadi sangat penting diteliti untuk mengetahui bagaimana Integrasi tasawuf dalam kurikulum pendidikan islam. Pendekatan yang digunakan dalam penelitian ini adalan pendekatan kualitatif, Teknik pengumpulan data pada penelitian ini dilakukan dengan dokumentasi dan Teknik analisis data yang digunakan dalam penilitian ini adalah model Miles dan Huberman. Hasil dari penelitian ini bahwa tarekat yang diajarkan dipesantren ini adalah tarekat qodiriyah wa Naqsabandiyah, terdapat Pendidikan formal dan non formal, serta terjadi integrasi Ajaran tarekat dalam kurikulum Pendidikan islam. Pengajaran tarekat dilaksanakan diluar pembelajaran formal seperti pengajian sunnah, dzikir 165 kali setelah solat wajib, khususiyah dan manaqiban.